P131 Efficacy and safety of olokizumab in a phase III trial of patients with moderately to severely active RA inadequately controlled by methotrexate: placebo and active controlled study. (26th April 2021) - Feist, Eugen; Chohan, Saima; Fatenejad, Saeed; Grishin, Sergey; Korneva, Elena; Nasonov, Evgeniy L; Rowińska-Osuch, Anna; Samsonov, Mikhail
Abstract: Background/Aims Olokizumab (OKZ) is a new humanised monoclonal antibody targeting IL-6 directly. Here we present the results of a global randomised clinical trial (RCT) in patients (pts) with RA. Methods This double-blind, placebo (PBO) and active controlled, RCT in pts with moderately to severely active RA despite MTX (ClinicalTrials.gov Identifier NCT02760407, CREDO2) was carried out in 18 counties. Pts were randomized 2:2:2:1 to receive subcutaneous injections of OKZ 64 mg every 2 weeks (q2w), OKZ 64 mg once every 4 weeks (q4w), adalimumab (ADA) 40mg q2w or PBO for 24 weeks, plus MTX. After week 24, subjects either rolled over into an open-label study or entered the Safety Follow-Up Period for another 20 weeks. The primary endpoint was ACR 20% (ACR20) response rate at week 12. Secondary endpoints included: percentage of subjects with DAS28-CRP <3.2 and improvement of HAQ-DI from baseline at week 12, ACR50 and percentage of subjects with remission (CDAI) ≤2.8 at week 24. Safety outcomes, including adverse events, serious adverse events and laboratory abnormalities were assessed. Results 1, 648 subjects were randomised to OKZ 64mg q2w (n = 464), OKZ 64mg q4w (n = 479), ADA 40mg (n = 462) or PBO (n = 243). Baseline characteristics were comparable across treatment arms. The vast majority of the pts completed 24 weeks treatment period 421 (90.7%) in q2w, 437 (91.2%) in q4w, 413 (89.4%) in ADA and 208 (85.6%) in PBO arms and enrolled to open-label extension study: 410 (88.4%), 422 (88.1%), 397 (85.9%) and 199 (81.9%) pts, respectively. Both regimens of OKZ were significantly better than PBO in all primary and secondary endpoints. Furthermore, non-inferiority to ADA was demonstrated for the pre-defined endpoints of ACR20 and DAS28-CRP<3.2 for both OKZ treatment groups. The efficacy outcomes were maintained throughout the 24-week period of the study. Overall incidence of treatment-emergent adverse events (TEAEs) was 70.0% in OKZ q2w arm; 70.9% in OKZ q4w arm, 65.4% in ADA arm and 63.4% in PBO, TEAEs leading to study treatment discontinuation were reported in 4.5%, 6.3%, 5.6% and 3.7% pts, respectively. The number of deaths were comparable among arms: 3 (0.6%; 2 infections, 1 cerebrovascular accident) in the OKZ q2w arm, 2 (0.4%; 1 infection, 1 myocardial ischemia) in OKZ q4w arm, 1 (0.2%; infection) in ADA arm and 1 (0.4%; sudden death) in PBO. The most common treatment-emergent serious adverse events (TESAEs) were infections. Conclusion In this global Phase III trial, treatment with OKZ plus MTX in both regimes (OKZ 64 mg q2w and OKZ 64 mg q4w) was associated with significant improvements in the signs, symptoms and physical function of RA compared to PBO plus MTX and non-inferior to ADA plus MTX over a 24-week period. OKZ was well tolerated and no new safety signals were observed. Disclosure E. Feist: Consultancies; R-Pharm, Abbvie, BMS, Celgene, Janssen, Lilly, Medac, MSD, Novartis, Pfizer, Roche/Chugai, Sanofi. Honoraria; R-Pharm, Abbvie, AB2Bio, BMS, Celgene, Janssen, Lilly, Medac, MSD, Novartis, Pfizer, Roche/Chugai, Sanofi, Sobi, UCB. Member of speakers' bureau; R-Pharm, Abbvie, AB2Bio, BMS, Celgene, Janssen, Lilly, Medac, MSD, Novartis, Pfizer, Roche/Chugai, Sanofi, Sobi, UCB. Grants/research support; Lilly, Novartis, Pfizer, Roche/Chugai. S. Chohan: None. S. Fatenejad: Consultancies; RPharm International. Shareholder/stock ownership; Pfizer. S. Grishin: Corporate appointments; Employed by R-Pharm. E. Korneva: Corporate appointments; Employed by R-Pharm. E.L. Nasonov: Honoraria; Lilly, Abbnie, Prizer, Biocad, R-Pharm. Member of speakers' bureau; Lilly, Abbnie, Prizer, Biocad, R-Pharm. A. Rowińska-Osuch: Consultancies; R-Pharm. M. Samsonov: Corporate appointments; Employed by R-Pharm.